The Heroic Value of Characters in Jalu Kancana's Kekal Novel and Its Application in Learning Indonesian Language and Literature in Senior High School - Sulis; Efendi; Ade Nurul Izatti; Gazali; Nirmayanti (Universitas Islam Negeri Palopo, 2025)
This research aims to explain how these heroic values are reflected in the actions and characters of the main characters in the novel Kekal by Jalu Kancana and find out their application in language and literature learning at SMA Negeri 1 Parigi. This research was conducted using qualitative descriptive research with a content analysis method. The research focuses on the assessment of the value of hard work, the value of discipline, the value of independence, the value of independence, the value of cooperation, and the value of compassion, as well as to find out its application in Indonesian learning at SMA Negeri 1 Parigi. The results of the data findings found are in the form of quotes that contain elements of heroic values and educational values, referring to the theories of educational values of the types of data findings of each other, and after that the findings are in the form of quotes of educational values that have been expressed by experts. Next, it is grouped into the types of data findings, and after that the data findings are narrated. The next data findings will be observed by two teachers at SMA Negeri 1 Parigi. Based on the studies that have been carried out, it can be concluded that the novel Kekal by Jalu Kancana as a result of data findings amounted to 69 educational values, which were divided into the value of hard work amounting to 20 data citations, the discipline value of 8 data, the independent value of 6 data, the value of cooperation amounting to 13 data, and the value of affection 20 data. From the results of this research, the value of hard work, the value of affection, and the value of cooperation are very visible in this novel. Therefore, the novel Kekal Karya Jalu Kancana can be applied in Indonesian learning at SMA Negeri 1 Parigi. Thus, it can be concluded that the results of this research are suitable for application in the learning of Indonesian Language and Literature at SMA Negeri 1 Parigi.